Retention of Bioactive Compound in the Concentration of Centella Asiatica Extract through Progressive Freezing - Amran, N.A. (Institute of Physics Publishing, 2020)
Phenolics and flavonoids were the two major bioactive compounds in C.asiatica that contributes to its therapeutic values. However, concentration by evaporation resulted in denaturation of the compounds due to their heat sensitivity nature. Therefore, this paper aims to introduce progressive freezing (PF) process as a new concentration method for the C.asiatica. PF separates two liquid compounds based on their freezing point difference. One with a higher freezing point would solidify first while another one would remain as a liquid. Low temperature involved in this process could minimize the heat abuse to the volatile compounds of C.asiatica. In this study, maceration was done to get the C.asiatica extract by preparing 1:80 ratio of solute to solvent and stirred at 1200 rpm for 24 hours. On the other hand, the PF was conducted in a cylindrical stirred crystallizer. For PF process, two operating parameters which are coolant temperature ranging from -6°C to -12°C, and stirring rate ranging from 100 rpm to 250 rpm have been tested for their effects towards the process performance. Two determinant parameters which were effective partition constant, K and retention efficiency (Reff) of bioactive compounds (flavonoid and phenolic) in the concentrated solution had been used to portray the process efficiency. On completing the experimental work, it was found that lower coolant temperature, and a moderate stirring rate resulted in the higher concentration efficiency of the bioactive compounds. The highest concentration efficiency of 69 and the smallest effective partition constant (K) of 0.51 were achieved at -10°C, 150 rpm and 30 minutes. © 2020 IOP Publishing Ltd.